Pengaruh Transfer Pricing Terhadap Tax Avoidance Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Siburian, Valentina N.C; Nisa, Farhatun (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of transfer pricing on tax avoidance with institutional ownership as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period The analysis method used is moderating regression analysis with a quantitative approach using Eviews 12 software. The research sample was selected using a purposive sampling technique for mining companies that had complete and relevant data during the research period.